Should cancer pain still be considered a separate category alongside acute pain and chronic non-cancer pain? Reflections on ICD-11 - Bäckryd, Emmanuel (Frontiers in Pain Research, 2024)
Introduction: Traditionally, cancer pain has often been viewed as an independent third major category in pain medicine alongside acute pain and chronic non-cancer pain. However, the new chronic pain category MG30 in the eleventh version of International Classification of Diseases (ICD-11) includes cancer-related pain as one of its seven subgroups. In light of this, the aim of the paper is to investigate whether the traditional trichotomy should be replaced by a dichotomy between acute pain and chronic pain, cancerrelated pain being part of both groups depending on the duration of pain. Methods: The rationale for viewing cancer pain as a separate category is reviewed. Results: Cancer being a deadly disease, cancer pain has a life-and-death and existential dimension that is different from non-cancer pain. It seems sensible to believe that this is an additional dimension to the suffering caused by cancer pain, and that clinicians should therefore take this existential dimension into consideration when assessing pain. Conclusion: Without challenging the place of chronic cancer-related pain under the MG30 heading, it is concluded that while using ICD-11 in the future, pain clinicians should continue being mindful of the fact that the reality of death shapes the experience of cancer pain. The traditional trichotomy is therefore still valid and mirrors the fact that human beings are vulnerable (acute pain), temporal (chronic pain) and mortal (cancer pain).